Dante's Commedia Elements of Structure - Singleton, Charles S. (Johns Hopkins University Press, 2019)
Originally published in 1977. This book contains four essays by Professor Charles Singleton: "Allegory," "Symbolism," "The Pattern at the Center," and "The Substance of Things Seen." These four essays treat four dimensions of meaning essential to understanding the substance and special texture of the poetry of the Divine Comedy. One might speak of "facets" or "aspects" of meaning if such terms did not suggest surface reflections dependent on the way a work (as a jewel) is turned for inspection. But for Singleton, each dimension has a depth that reaches to the core and substance of Dante's poetry, so they are, in Singleton's view, elements of its structure.